Acceleration of vortex methods calculation using MDGRAPE-2 and MDGRAPE-3: A comparative study (Daffodil International University Journal of Science and Technology, 2010)
The calculation of vortex method has been accelerated by using special-purpose computers, MDGRAPE-2 and MDGRAPE-3, respectively. The similar algorithm has been implemented and the improvement in speed of MDGRAPE-2 was 100 times while MDGRAPE-3 was 1000 times faster when compared with the ordinary PC Xeon 5160(3.0GHz) for N=106. In addition, the speed of MDGRAPE-3 was 25 times faster compared with MDGRAPE-2. The round off errors have been investigated in both cases. Keywords: Vortex Method, Special-Purpose Computer, MDGRAPE-2, MDGRAPE-3, Scaling Error   DOI: 10.3329/diujst.v4i1.4351 Daffodil International University Journal of Science and Technology Vol.4(1) 2009 pp.23-27